MODEL PEMBELAJARAN SSCS BERBANTU FLASHCARD TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA MATERI SISTEM EKSKRESI - Rintin Irmayani; Milla Listiawati; Sri Maryanti (Universitas Sebelas Maret, 2025)
This research was motivated by the low problem solving abilities of students. Therefore, one way to overcome thisproblem is to use the SSCS model. This research aims to determine students' problem solving abilities using theSSCS model assisted by flashcards. The method used is a quasi experiment with a non-equivalent control groupdesign, and uses a quantitative approach. The sample was selected using purpoive sampling technique. The researchresults showed that the problem solving abilities of experimental class students obtained an average pretest score of39.7 and an average posttest score of 71.7. Meanwhile, the control class obtained an average pretest score of 40.2and an average posttest score of 61.7. As well as the average posttest score for each indicator of problem solvingability in the experimental class and control class, the highest was the indicator of preparing a solution plan, and thelowest was the indicator of understanding the problem. The results of the prerequisite tests, namely the normalityand homogeneity tests, obtained that the pretest and posttest scores in the experimental class and control class werenormally distributed and had a homogeneous variance. Based on the hypothesis with the Independent Simple T-Test where sig results were obtained. (2-tailed) is 0.000 < 0.05 so that H0 is rejected and H1 is accepted, thus it canbe concluded that there is a difference between classes with and without using the SSCS model assisted by flashcardson problem solving abilities in the excretory system material.